PENERAPAN BIMBINGAN KELOMPOK TEKNIK HOME ROOM UNTUK MENINGKATKAN PENDIDIKAN SEKSUALITAS PESERTA DIDIK KELAS VIII - Ramadanti, Dita Cahya; Hidayat, Wahyu; Ningrum, Devy Sekar Ayu (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
Home room technique group guidance is the creation of a family atmosphere in group guidance services so that students are comfortable and not awkward when discussing. Comfort in a family atmosphere makes the topic of sexuality education no longer taboo to discuss. This study aims to improve the understanding of sexuality education in order to prevent the occurrence of risky sexual behavior of adolescents who are dating. This research method is a mixed method explanatory design. The sample of the study was 8 students of grade VIII of PGRI Ganjar Sabar Junior High School. The results of this study show that through the implementation of group guidance of home room techniques, it can improve the sexuality education of learners. Evidenced by the results of the t test which obtained a significance value of 2 tailed, which is 0.000 < 0.05.